Intraoperative Heparin Bolus and Postoperative Anticoagulation with Low Molecular Weight Heparin Increase Reliability of Microsurgical Free Flaps for Upper Extremity Reconstruction - Kallenberger, Ann-Katrin; Xiong, Lingyun; Gazyakan, Emre; Ziegler, Benjamin; Will, Patrick; Kneser, Ulrich; Hirche, Christoph (Journal of Reconstructive Microsurgery, 2022)
Background Microsurgery is an indispensable tool of upper extremity reconstruction addressing defect coverage and the restoration of function. Perioperative anticoagulation and antiplatelet therapy are controversially discussed with impact on microsurgical outcome, but without clear evidence. This study aims to evaluate the impact of perioperative anticoagulation and antiplatelet therapy in microsurgical upper extremity reconstruction.Methods All eligible patients treated with microsurgical upper extremity reconstruction between January 2000 and July 2014 were included in a comparative analysis to define a superior anticoagulation and antiplatelet regime in a retrospective study. Endpoints were all major complications (e.g., total flap loss, arterial and venous thrombosis) as well as minor complication.Results A total of 183 eligible free flaps to the upper extremity were transferred in 169 patients. Altogether, 11 arterial (6.0%) and 9 venous (4.9%) thromboses, 11 total flap losses (6.0%), and 16 cases with hematoma (8.7%) were detected. In the subgroup analysis, patients who did not receive any heparin intraoperatively (n = 21; 11.5%) had a higher rate of major complications (p = 0.001), with total flap loss being the most frequent event (p = 0.004). A trend was shown for intraoperative bolus administration of 501 to 1,000 units unfractionated heparin (UFH) intravenously to have the lowest rate of major complications (p = 0.058). Intraoperative administration of acetylsalicylic acid (n = 13; 8.1%) did not have any influence on the rate of major complications. Postoperative anticoagulation with continuous UFH intravenously (n = 68; 37.2%) resulted in more frequent complications (p = 0.012), for example, an increased rate of total flap loss (p = 0.02) and arterial thrombosis (p = 0.02).Conclusion The results of the present study favor administration of 501 to 1,000 units UFH intravenously as an intraoperative bolus (e.g., 750 units UFH intravenously). Postoperative low molecular weight heparin subcutaneous application in a prophylactic dose given once or twice a day was associated with less complications compared with continuous infusion of UFH, although continuously applied UFH may reflect an increased risk profile.
Keywords: free flap; upper extremity; heparin; anticoagulation; antiplatelet; low molecular weight heparin (LMWH)